The creativity of learners through process learning project based learning (PJBL) in SMAN Krueng Barona Jaya - Tria Maulida; Ismul Huda; M Ali S (Jurnal Edubio Tropika, 2018)
This study was designed to determine the comparative creativity of learners who follow PjBL in the environment around with students who follow PjBL in the classroom. The study was conducted from May 2016 to May 2017. The study used a descriptive approach with experimental research type. Design in research is simple factorial design 2x2. The sample of the study amounted to 121 students. The instrument of research in the form of observation sheet of creativity of learners. Data were analyzed by the non-parametric statistical test of Mann Whitney U at a significant level of 0.05. The results showed that the creativity of students Z = 9.179 and Z = 7.563 which means the value of Z ˃ Z-table =1,96 means that the application of PjBL model in the class and in the environment has a significant effect on the creativity of the students. It can conclude that students who follow PjBL in the environment show significantly better creativity than students who follow PjBL in the classroom.